2013
DOI: 10.1021/jp4043232
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition of Poly(N-isopropylacrylamide) in Aqueous Protic Ionic Liquids: Kosmotropic versus Chaotropic Anions and Their Interaction with Water

Abstract: We have investigated the influence of a series of triethylammonium-based protic ionic liquid-water solutions on the lower critical solution temperature (LCST) of poly(N-isopropylacrylamide) (PNIPAM). We find that kosmotropic anions lower the LCST of PNIPAM more dramatically when compared with chaotropic anions. In addition, we have probed the solvent properties of the hydrated protic ionic liquid solutions using (1)H NMR, polarity measurements, and solvatochromic analysis of the Kamlet-Taft parameters, β and π… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 54 publications
2
31
0
Order By: Relevance
“…It was observed that the kosmotropic anions of H 2 PO 4 − and HSO 4 − caused a large downfield shift, indicative of strong interactions between the PILs and water, the fluorinated Tf and BF 4 had only weak interactions with water, attributed to their hydrophobicity, and no interaction was observed for chaotropic anions. 129 An FIR investigation showed that the strong anion−cation interactions present in triethylammonium methylsulfonate required a minimum of four water molecules to begin to be disrupted. 130 When the anion of trifluoromethylsulfonate is paired with the triethylammonium cation, then the cation−anion interaction is weaker, and less water is required to disrupt the interaction.…”
Section: Solvent Mixtures Containing Pilsmentioning
confidence: 99%
“…It was observed that the kosmotropic anions of H 2 PO 4 − and HSO 4 − caused a large downfield shift, indicative of strong interactions between the PILs and water, the fluorinated Tf and BF 4 had only weak interactions with water, attributed to their hydrophobicity, and no interaction was observed for chaotropic anions. 129 An FIR investigation showed that the strong anion−cation interactions present in triethylammonium methylsulfonate required a minimum of four water molecules to begin to be disrupted. 130 When the anion of trifluoromethylsulfonate is paired with the triethylammonium cation, then the cation−anion interaction is weaker, and less water is required to disrupt the interaction.…”
Section: Solvent Mixtures Containing Pilsmentioning
confidence: 99%
“…More compact (smaller dimensions) and better defined (narrower size distribution) particles are obtained by abrupt, shock heating. Size reduction is observed upon addition of a surfactant, 19 ionic liquids, 20 and osmolyte. 21 The ideal system for preparation of nanocapsules via mesoglobule templates should possess the following characteristics:…”
Section: Preparation Of Polymeric Nanocapsulesmentioning
confidence: 99%
“…The β of ILs and IL–water mixtures were measured and calculated from the absorption peaks of the dyes as described . Experimental conditions were slightly modified based on methanol and water, and the obtained values were in good agreement with the literature .…”
Section: Methodsmentioning
confidence: 99%